Comparison of meibomian gland dropout using two infrared imaging devices. Issue 3 (June 2019) - Wong, Stephanie; Srinivasan, Sruthi; Murphy, Paul J.; Jones, Lyndon
Highlights: Meibography was performed with two different commercially available meibographers. Images were analyzed with a subjective grading scale and semi-objectively using ImageJ. Significantly less gland loss was found with the LipiView II than the Keratograph 5 M. Varying amounts of dropout were observed due to differences in images quality and different lid eversion techniques. Abstract: Purpose: To measure the degree of meibomian gland (MG) dropout in the lower eyelid determined by analysis of images obtained from the LipiView II (LVII) and the Keratograph 5M (K5M). Methods: The inferior eyelid of each participant was imaged in a random order using both devices. All images were subjectively assessed by a single-masked investigator to determine the extent of MG loss using the Arita 4-point meiboscore grading scale. The images were also semi-objectively analyzed with ImageJ to calculate the percentage of MG dropout, by tracing around the non-glandular area and the total exposed area of the lower lid. Results: Twenty participants (mean age 37 years, range 23–60, 60% female) completed the study. A significant difference in meiboscore (mean ± SD) was obtained between the LVII and the K5M (1.43 ± 0.78 vs. 1.90 ± 0.81, Z = 3.25, p = 0.001). The meiboscore 95% limit of agreement (LOA) ranged from −1.88 to +0.93. A significant difference was found with mean ImageJ percentage dropout between the LVII and the K5M (31.5% vs 43.4%, t = −4.8, p = 0.00003). The percentage dropout 95% LOA ranged from −42.79% to +19.06%. Conclusions: LVII images had significantly lower meiboscores and less percentage MG dropout. Varying amounts of dropout were observed between the devices due the amount of eyelid that was typically everted and because of differences in image quality. These results indicate that these devices should not be used interchangeably to evaluate MG dropout.